Demographic features of acute drug poisoning admitted to Inonu University Hospital in Malatya, Turkey - Oguzturk, Hakan; Turtay, Muhammet Gokhan; Pamukcu, Esra; Ciftci, Osman (Academic Journals, 2010)
In this study, the patients appealed to Emergency Medicine Department, Faculty of Medicine, University of Inonu, Malatya, Turkey because the acute drug poisoning in the period from 01/01/2008 to 31/12/2009 were evaluated retrospectively. Demographic features of the patients, the agent responsible for poisoning and hospitalization rates were assessed. In this aim, we evaluated 178 patients, ages ranged from 18 to 77.79 (44.4%) were men and 99 (55.6%) patients were women. The mean ages of male and female were found to be 32.2 +/- 12.2 and 31.3 +/- 12.0, respectively. 91(51.1%) patients were living in rural areas and 87 patients (48.9%) were living in urban centers. It was found that 156 (87.6%) of these patients had first poisoning whilst 19 (10.7%) patients experienced second poisoning event and 3 (1.7%) patients had third poisoning event. The type of the poisoning was ingestion of drugs for suicidal intent in 146 (82%) cases and accidental ingestion in 32 (18%) cases. Poisoning most commonly occurred as ingestion of multiple drugs. Seven patients (3.9%) were discharged from the emergency service (ED), while 132 patients (74.2%) were hospitalized in intensive care unit of anesthesiology and 39 patients (21.9%) in the department of internal medicine. Average duration of hospitalization of all patients was 3.46 +/- 2.22 days. Drugs poisoning occur most frequently as ingestion of multiple drugs in young individuals and female.
Keywords: Emergency department; drug poisoning; demographical features; Turkey